Analisis Munafik dalam Tafsir Al-Jami'li Ahkamil Quran: Studi Thematic Surat Al-Baqarah Verses 8-20 - Didik Hariyanto,; Mahfud,; Hizbullah Maulana Al-Farizy, (Technium Education and Humanities, 2024)
Hypocrites are one of the groups that have the potential to damage the unity and integrity of Muslims in the world. The Qur'an discusses this issue of hypocrisy extensively. Therefore, the authors conclude that an understanding of this hypocrisy is very important for the general public. Thus, the author aims to review the concept of hypocrisy in the view of Imam Abu Abdillah Al-Qurthuby based on this explanation. In this study, the author also used a library approach. His research methods involved a thematic approach to figures, focusing on the views of Al-Qurthuby and other scholars. Practically, the author will investigate the concept of hypocrisy taking into account the views of Al-Qurthuby. In addition, the author will present information about the background, education, and influence of Al-Qurthuby teachers in this study. This study also formulated research questions, namely how Al-Qurthuby interprets the verses of Al-Baqarah 8-20, and how Al-Qurthuby interprets the concept of hypocrisy in the tafsir of Al-Jami' li Ahkamil Qur'an. The conclusion of the study states that in the view of Imam Al-Qurthuby, hypocrites are individuals who only show faith verbally. They express their beliefs in words, but in fact their hearts and beliefs reject the Sharia that has been revealed by Allah. They have qualities that are very displeased by Allah, and as a result, they will receive torment in the afterlife.